Association of Hb A2 Variants with Several Forms of α- and β-Thalassemia in Thailand - Sitthichai Panyasai (2020)
© 2020 Informa UK Limited, trading as Taylor & Francis Group. In this study, Hb A2 variants and their association with α- and β-thalassemia (α- and β-thal) were analyzed. We performed molecular analyses to identify α-thal [– –SEA (Southeast Asian),––THAI (Thai), –α3.7 (rightward) and –α4.2 (leftward)] deletions, and Hb Constant Spring (Hb CS; HBA2: c.427T>C), Hb A2-Melbourne (HBD: c.130G>A), Hb A2′ (HBD: c.49G>C), Hb A2-Lampang (HBD: c.142G>A). β0-Thalassemia mutations included codon 17 (A>T) (HBB: c.52A>T), codons 41/42 (–TCTT) (HBB: c.126_129delCTTT), codons 71/72 (+A) (HBB: c.216_217insA) and IVS-I-1 (G>T) (HBB: c.92+1G>T) in 23 samples which had a Hb A2 variant peak in zone 1 of the capillary electrophoresis (CE) electropherogram. Results showed that 20 patients (87.0%) carried Hb A2-Melbourne with seven different genotypes for α- and β-thal, two (8.7%) carried Hb A2′ and one (4.3%) carried Hb A2-Lampang. All three samples doubly heterozygous for Hb A2-Melbourne/β0-thal had Hb A2 levels lower than 4.0%, while summation of Hb A2 and Hb A2-Melbourne ranged from 4.9–5.3%, reaching the accepted range (4.0–10.0%) for β-thal trait. Hb A2-Melbourne is the most common δ-globin variant in the Thai population. Hb A2 variant and Hb A2 levels must be combined in order to diagnose carriers of β-thal. β-Globin haplotype analysis showed an association with a single β-globin haplotype [+–––– + +] of Hb A2-Melbourne, Hb A2′ and Hb A2-Lampang, indicating that they were of the same origin. We developed a multiplex allele-specific polymerase chain reaction (ASPCR) for simultaneous detection of these three Hb A2 variants.